Image intensifiers - Ford, Sara; Games, Martin Hughes (Bristol : BBC-TV Production [production company] ; London : BBC Education & Training [distributor], 1994)
Describe on different ways of creating, build and intensive an image. Also explain on history of intensive an image by nature
Produced by BBC-TV Production in association with Lionheart Television International
Copy available in DVD format
Film editor, Peter Brownlee
Narrator: Richard Jobson
Keywords: Image intensifiers